IDENTITY CONVERGENCE IN THE TAPESTRY AND PAINTING OF ECATERINA AJDER - Constantin SPÎNU (Academy of Sciences of Moldova, 2021)
Ecaterina Ajder, representative of the early `80s of plastic artists from the Republic of Moldova, constantly opts for endowing the work of art with innovative stylistic values. Plastic tradition and modernity originally connect in her creation, contributing to the generation of current messages through image. Preferring to materialize her thematic and plastic predilections in the genre of artistic tapestry and easel painting, Ecaterina Ajder has drawn and consolidated over the decades her unmistakable stylistic facet, in which the insurmountable landmarks of folk art have found a favorable artistic fulfillment and integration into relevant contemporary creative trends. In the artistic tapestry, the painter significantly capitalized both the aesthetic expressions obtained from the classic weaving, and from combining it with various techniques such as felt and embroidery. When referring to the easel painting she highlighted the traditional aspects of structural-constructive constitution of the image field and, at the same time, the impressive artistic expressions, obtained after practicing mixed techniques, giving priority to the collage methodology. In the artist’s creation, both the conceptualization and aesthetic interpretation of the theme, as well as the way of operating with plastic means imminently contribute to the demarcation and supplementing of the semantic area of the work with high value expressions.